2014
DOI: 10.3389/fnagi.2014.00159
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of vascular risk burden and advanced age on cerebral blood flow

Abstract: Vascular risk factors and cerebral blood flow (CBF) reduction have been linked to increased risk of cognitive impairment and Alzheimer's disease (AD); however the possible moderating effects of age and vascular risk burden on CBF in late life remain understudied. We examined the relationships among elevated vascular risk burden, age, CBF, and cognition. Seventy-one non-demented older adults completed an arterial spin labeling MR scan, neuropsychological assessment, and medical history interview. Relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 67 publications
3
65
1
Order By: Relevance
“…Taken together, these limitations may explain some of the seemingly contradictory findings in AD risk and AD-related ASL studies, including inconsistencies regarding hyperperfusion and hypoperfusion and regional differences in CBF alteration between studies. Other possible explanation for disparate findings in AD-related CBF research include patient demographics (i.e., age and vascular risk burden (Bangen et al 2014)), disease severity, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these limitations may explain some of the seemingly contradictory findings in AD risk and AD-related ASL studies, including inconsistencies regarding hyperperfusion and hypoperfusion and regional differences in CBF alteration between studies. Other possible explanation for disparate findings in AD-related CBF research include patient demographics (i.e., age and vascular risk burden (Bangen et al 2014)), disease severity, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated vascular risk burden, or the presence of vascular risk factors (e.g., diabetes, hypertension, heart disease, current smoking), is associated with an increased risk of cognitive decline and AD (Luchsinger et al 2005; Austin et al 2011; Gorelick et al 2011; Bangen et al 2014). Moreover, AD risk increases with the number of coexisting vascular risk factors present (Luchsinger et al 2005).…”
Section: Resting Cbf In Vascular Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reviewed above tend to suggest hyperperfusion precedes hypoperfusion in earlier phases of disease development and progression (Figure 1) [23,36,37,40]. Some differences across studies may be attributable to methodological differences, such as CBF collection methods, patient demographics such as age and vascular risk burden [54], diagnostic criteria for MCI, disease severity, or misclassifying preclinical AD as normal controls. It is also possible that differences in the way CBF is coupled with local metabolic needs during different phases of disease development and progression may explain this paradoxical, biphasic early hyperperfusion followed by later hypoperfusion CBF response.…”
Section: Resolving Inconsistent Findings Of Hypoperfusion and Hypementioning
confidence: 99%
“…Numerous investigations have shown that LOAD risk is increased in the presence of antecedent cardiovascular (CV) risk factors, such as history of type 2 diabetes (T2D), 2,3 hypertension, smoking, 4 lipid disorders, 5 and cerebrovascular factors, alone or in aggregate. 6 Some studies suggest that CV disease (CVD) may affect dementia through multiple mechanisms, including reduction in cerebral blood flow 7 and breakdown of the blood-brain barrier. 8 …”
mentioning
confidence: 99%